Increased IL-17 and IL-21 producing TCRαβ+CD4−CD8− T cells in Chinese systemic lupus erythematosus patients. (June 2014) - Wang, H-X; Chu, S; Li, J; Lai, W-N; Wang, H-X; Wu, X-J; Kang, X; Qiu, Y-R
Background : Increased numbers of TCRαβ + CD4 − CD8 − T cells in the peripheral blood of systemic lupus erythematosus (SLE) patients in the United States and United Kingdom have been reported. However, the proportions of TCRαβ + CD4 − CD8 − T cells and their involvement in the pathogenesis of SLE in Chinese populations are yet to be determined.Methods : A total of 120 SLE patients, 38 rheumatoid arthritis (RA) patients and 43 normal control subjects were examined. The proportion of TCRαβ + CD4 − CD8 − T cells in the peripheral blood, Fas expression on these cells, and intracellular cytokine levels in these cells were assessed using flow cytometry. Plasma cytokine concentrations were measured using enzyme-linked immunosorbent assay.Results : The percentages of TCRαβ + CD4 − CD8 − T cells were increased in Chinese SLE patients, particularly in active SLE patients, correlated with decreased Fas expression on these cells. IL-17 and IL-21 levels in the blood and in TCRαβ + CD4 − CD8 − T cells from SLE patients were increased. Moreover, a positive correlation was evident between IL-17- and IL-21-producing TCRαβ + CD4 − CD8 − T cells.Conclusions : Increased TCRαβ + CD4 − CD8 − T cells expressing inflammatory cytokines, such as IL-17 and IL-21, may be implicated in the pathogenesis of SLE in patients. Appropriate IL-17- and/or IL-21 blockage may be utilized as a novel immunotherapeutic strategy for SLE patients.